OBSERVATIONS ON THE FREQUENCY OF INTRASEASONAL MATURITY AND BUNDH BREEDING OF LABEO ROHITA (HAM) AND CIRRHINUS MRIGALA (HAM) AT SONEPUR, ORISSA - Badapanda, H S; Das, P K; Patnaik, G C (Indian Journal of Fisheries, 2011)
During July, 1980, natural spawning of Labeo rohita (Ham) and Cirrihinus mrigala (Hani) have been observed en masse both in dry and wet bundhs for the first time in Orissa. The brood stock kept in distressed condition during summer months have spawned naturally in early part of monsoon. Feeding with groundnut oil-cake at 0.5% (before spawning) and at 1.0% (after spawning) of body weight of the fishes has helped in secondary intra-seasonal maturity after a period of 49 days. These gravid fish have been found to spawn naturally again in the wet bundh after a gap of 64 days. Such observations have been recorded for the first time in India. Topography and soil texture of the bundhs and environmental physico-chemical factors at the time of spawning have been discussed